A review on single crystal and thin film Si–Ge alloy: growth and applications. Issue 11 (25th May 2022) - Basu, Ranita
Abstract : Dual application of Si–Ge alloy in thermoelectric and BICMOS in the semiconductor industry. Abstract : The IV–IV binary alloy, Si–Ge, has attracted incredible attention for its superior performances in multiple disciplines, especially in high temperature thermoelectric and BICMOS applications in the semiconductor industry. Although the alloy perceptibly exhibits a complete miscible system that can realize Si–Ge crystals with any Ge contents, the wide gap between the solidus and liquidus line inhibits the formation of Si–Ge bulk crystal with uniform Ge content. Several synthesis procedures were adapted to counteract the single crystal Si–Ge with a homogeneous composition. Although polycrystalline Si–Ge finds wide application in thermoelectric applications, single crystal silicon–germanium has proved to be the most economic, unconditional transceiver chipset resolution to uplift the future soaring bandwidth requisite for wireless backhaul information transmission. In addition, the superior electronic mobility in Si–Ge in contrast to Si has established its place in telecommunication, computer technologies, consumer electronics, space, and aerospace applications. Herein, we comprehensively summarize the development in the synthesis of bulk and thin film single crystal Si–Ge with uniform composition to be used in thermoelectric applications, especially in space applications and as heterojunction bipolar transistors to form a Si–Ge heterojunction bipolar transistor (HBT) BiCMOS technology. Thus, this expertise is expanding into diverse end-markets owing to telecom, automobile, solar, and thermoelectric capabilities. The perspective for improving the performance of the binary IV–IV alloy is also provided as a model for future development and applications in the thermoelectric and semiconductor industry.